Jurisdição constitucional sem supremacia judicial: a reconciliação entre a proteção de direitos fundamentais e a legitimidade democrática no constitucionalismo - Lucas Azevedo Paulino (2016)
The aim of this dissertation is to analyze the best normative justification for the exercise of judicial review in a democracy. In a context of expansion of the operation of the judiciary and of the constitutional courts in the judicial review of legislation - and, in some cases, of constitutional amendments - in Brazil and in several countries, often deciding on matters of strong moral, political and social appeal, criticism on the democratic legitimacy of the court's authority arise. Considering the persistence of good faith moral disagreement in a democratic and pluralistic society on the meaning of rights, should a constitutional court have the final word on constitutional interpretation? This dissertation intends to investigate, how to reconcile the effective protection of fundamental rights with the democratic exercise of power. Initially, the two traditional responses from constitutional and democratic theory and the practice concerning the legitimacy (or the lack thereof) of judicial supremacy in a democratic regime will be studied. The research, firstly, discusses the legal conception of constitutionalism and its constitutional conception of democracy, which justifies the role of constitutional jurisdiction, especially having regard to the substantive outcomes that can provide to protect fundamental rights. In this respect, the emphasis of research will be on the works of Ronald Dworkin and John Rawls. Secondly, this study presents the political constitutionalism and its majoritarian conception of democracy, which is especially concerned with the intrinsic legitimacy of procedures, with the observance of political equality and the self-government of the people. The theories of Jeremy Waldron and Richard Bellamy will be the subject of examination in this part. After having developed the main arguments for and against the role of courts and parliaments, this dissertation analyzes characteristics and the normative potential of the new Commonwealth model of constitutionalism, pointed out by Stephen Gardbaum as an intermediate solution which dissociates the control of constitutionality from judicial supremacy, by granting the final word to the legislature. Finally, this dissertation analyzes the proposal for the Constitutional Amendment No. 33/11 and whether it could improve the democratic legitimacy of the Brazilian constitutional system.